2020
DOI: 10.1891/clinlact-d-20-00001
|View full text |Cite
|
Sign up to set email alerts
|

Using the Preterm Infant Breastfeeding Behavior Scale With Late Preterm Infants

Abstract: BackgroundFeeding effectiveness of late preterm infants may vary between feedings and over time creating confusion and frustration for parents and clinicians. An assessment tool for late preterm infants may assist mothers to recognize breastfeeding behavior more clearly. Although tools are available, none have been tested specifically with late preterm infants. We sought to determine the inter-rater reliability of the Preterm Infant Breastfeeding Behavior Scale scores for late preterm infants between mothers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…(6) Diversos estudos têm mostrado a escala PIBBS como um dos instrumentos confiáveis para avaliar o comportamento de amamentação em recém-nascidos pré-termo. (3,(9)(10)(11) Estudo piloto a fim de determinar a confiabilidade interavaliadores das pontuações de avaliação da PIBBS na observação do comportamento de recém- -nascidos entre 34 a 36 semanas de idade gestacional e entre mães e profissionais de saúde, mostrou que os seis componentes da escala PIBBS foram pontuados de forma independente e a concordância variou de 81.8% a 100% para todos os itens. (9) Com o objetivo de descrever a amamentação e deglutição de um recém-nascido de 42 semanas de idade gestacional com diagnóstico de encefalopatia hipóxia isquêmica leve, da admissão à alta hospitalar foi utilizada a escala PIBBS para monitorar o progresso da amamentação por mães e profissionais de saúde, do sexto ao décimo terceiro ao dia de vida.…”
Section: Discussionunclassified
“…(6) Diversos estudos têm mostrado a escala PIBBS como um dos instrumentos confiáveis para avaliar o comportamento de amamentação em recém-nascidos pré-termo. (3,(9)(10)(11) Estudo piloto a fim de determinar a confiabilidade interavaliadores das pontuações de avaliação da PIBBS na observação do comportamento de recém- -nascidos entre 34 a 36 semanas de idade gestacional e entre mães e profissionais de saúde, mostrou que os seis componentes da escala PIBBS foram pontuados de forma independente e a concordância variou de 81.8% a 100% para todos os itens. (9) Com o objetivo de descrever a amamentação e deglutição de um recém-nascido de 42 semanas de idade gestacional com diagnóstico de encefalopatia hipóxia isquêmica leve, da admissão à alta hospitalar foi utilizada a escala PIBBS para monitorar o progresso da amamentação por mães e profissionais de saúde, do sexto ao décimo terceiro ao dia de vida.…”
Section: Discussionunclassified
“…The PIBBS is a tool used to monitor six specific behaviors of breastfeeding infants: rooting, areolar grasp, latch-on, sucking, longest sucking burst, and swallowing. Inter-observer reliability tests have shown that the PIBBS is a reliable instrument (Lober et al, 2020 ), but proper training is required for observers to use it effectively. In addition, while PIBBS is equipped with a guideline for behavior coding, PIBBS does not include a tutorial video for new coders or real-time observation features.…”
Section: Discussionmentioning
confidence: 99%
“…We now assess the quality of the breastfeeding by using the Fleur de Lait", 1 a breastfeeding scale derived from the Premature Infant Breastfeeding Behaviour Scale (PIBBS). 2 To proceed safely and cautiously, we tested this new protocol first on stable late preterm infants. Of course, we help parents acquire progressive autonomy in the use of this method which works as follows:…”
Section: Supporting Breastfeedingmentioning
confidence: 99%